A fire resistant cable having a multi-layer fire resistant construction
By designing a multi-layer fire-resistant structure in the cable, utilizing a continuous and dense barrier of porous carbon layers and molten glass phases, the problem of insufficient fire resistance time of the cable was solved, enabling the cable to operate normally for a long time in a fire.
Patent Information
- Application Number
- CN202611247025.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-11-03
AI Technical Summary
Existing fire-resistant cables have a short fire resistance time, which cannot meet the requirements for long-term normal operation during a fire.
The cable adopts a multi-layer fire-resistant structure design, including a fire-resistant mica filling layer, a flame-retardant shielding layer, and a fire-resistant and flame-retardant sheath layer. A porous carbon layer is synthesized on the surface of mica powder. A combination of borosilicate glass powder and modified mica powder is used to form a continuous carbon layer and a dense ceramic barrier layer. Combined with a composite flame-retardant system of epoxy resin E51 and carbon fiber, the fire resistance of the cable is improved.
It significantly enhances the fire resistance of the cable, delays the thermal damage of the inner insulation layer, provides high-strength fire protection, reduces interlayer gap defects, and ensures stable operation of the cable at high temperatures.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of fire-resistant cable technology, specifically to a fire-resistant cable with a multi-layer fire-resistant structure. Background Technology
[0002] Fire-resistant cables are cables that can maintain safe operation for a certain period of time under flame combustion conditions. They are used in fixed laying locations with fire resistance requirements. The products mainly include flame-retardant fire-resistant wires and cables, non-flame-retardant fire-resistant wires and cables, and mineral-insulated fire-resistant cables. They are widely used in high-rise buildings, subways, large power plants, and other places related to fire safety. They are electrical equipment used to transmit electrical energy, electrical signals, and realize electromagnetic energy conversion, and include four parts: conductor, insulation layer, shielding layer, and sheath layer.
[0003] The conductor of a fire-resistant cable is usually made of a highly conductive metallic material, which carries current and enables the transmission of electrical energy or signals. The insulation layer is a material with good insulation properties, wrapped around the conductor to prevent current leakage and short circuits between different conductors, ensuring the safety and stability of power transmission. The shielding layer is generally made of metallic materials and is mainly used to reduce the interference of the internal electromagnetic field of the cable to the outside world, while also preventing the influence of external electromagnetic fields on the internal signals of the cable, ensuring the quality of signal transmission. The sheath layer is located on the outermost layer of the cable and mainly serves a protective function.
[0004] However, in practical applications, the fire resistance time of cables is still relatively short, which cannot meet the requirements for long-term normal operation during a fire, thus limiting their application. Therefore, the fire resistance and high-temperature performance stability of existing cables still need to be further improved. Summary of the Invention
[0005] This invention provides a fire-resistant cable with a multi-layer fire-resistant structure, which solves the problem that the fire resistance time of the cable is still relatively short and cannot meet the requirements for long-term normal operation during a fire.
[0006] The technical solution of the present invention:
[0007] A method for preparing a fire-resistant cable with a multi-layer fire-resistant structure includes the following steps:
[0008] S1. Copper wire is stranded to obtain cable core material. Rubber insulation material is coated on the surface of the cable core material and cured to obtain insulated cable core material.
[0009] S2. Fire-resistant mica filler, fire-resistant shielding material and fire-resistant flame-retardant sheathing material are sequentially extruded onto the surface of the insulated cable core material to form a fire-resistant cable with a fire-resistant mica filler layer, a flame-retardant shielding layer and a fire-resistant flame-retardant sheathing layer on the surface in sequence, which is a fire-resistant cable with a multi-layer fire-resistant structure.
[0010] The fire-resistant mica filler is composed of ethylene-vinyl acetate copolymer, flame-retardant mica powder, dicumyl peroxide and polyethylene wax in a mass ratio of 10:(1.5-2):(0.1-0.2):(0.05-0.07).
[0011] The flame-retardant mica powder is obtained by synthesizing a porous carbon layer on the surface of mica powder, and then loading borosilicate glass powder to obtain modified mica powder; it is also obtained by mixing and reacting modified mica powder, aluminum hypophosphite, polyvinyl alcohol and chitosan.
[0012] The refractory shielding material is composed of ethylene-vinyl acetate copolymer, conductive carbon black, antioxidant 1010, polyethylene wax, and zinc borate in a mass ratio of 10:(3-5):(0.1-0.2):(0.2-0.4):(0.5-1).
[0013] The fire-resistant and flame-retardant sheath material is composed of epoxy resin E51, carbon fiber, curing agent, zinc phytate and aluminum acetate in a mass ratio of 10:(0.5-0.7):(1.2-1.5):(1-1.5):(1.2-1.6).
[0014] Further, in step S1, the stranding process specifically involves stranding 5-10 copper wires with a diameter of 2-3 mm together to form a cable core.
[0015] Furthermore, in step S1, the thickness of the rubber insulation layer is 0.5-1mm.
[0016] Further, in step S1, the curing process specifically involves curing at 150-190℃ and 8-10MPa for 2-4 hours.
[0017] Further, in step S2, the extrusion is carried out in an extruder, and the extrusion temperature of the refractory mica filler is 180-200℃; the extrusion temperature of the refractory shielding material is 160-180℃; and the extrusion temperature of the refractory flame-retardant sheath material is 140-160℃.
[0018] Furthermore, in step S2, the thickness of the fire-resistant mica filling layer is 1-2 mm; the thickness of the fire-resistant shielding layer is 1-2 mm; and the thickness of the fire-resistant and flame-retardant sheath layer is 3-4 mm.
[0019] Furthermore, the flame-retardant mica powder is specifically prepared by the following steps:
[0020] A1. Place mica powder in a mixture of glucose, potassium hydroxide and deionized water. After impregnation, remove it and dry it until the water evaporates. Place it in a tube furnace, introduce nitrogen gas, and carbonize it at 700-800℃ for 3-4 hours. Remove it, cool it to room temperature, wash it, and dry it until the water evaporates to obtain porous carbon-coated mica powder.
[0021] A2. Mix borosilicate glass powder and ethanol evenly, add porous carbon layer to coat mica powder, stir and adsorb at -0.05~-0.02MPa for 30-40min, filter, wash, and dry until ethanol evaporates to obtain modified mica powder.
[0022] A3. Dissolve chitosan and polyvinyl alcohol in an aqueous acetic acid solution, stir at 95-100℃ and 200-220r / min until completely dissolved, cool to room temperature, add glutaraldehyde, modified mica powder, and aluminum hypophosphite, stir at 1000-1500r / min for 5-10 min, and freeze-dry to obtain aerogel, i.e. flame-retardant mica powder.
[0023] Furthermore, in the above A1 reaction process, glucose and potassium hydroxide solution are mixed to form a mixed solution, and mica powder is impregnated into the mixed solution, so that glucose and activator potassium hydroxide coat the surface of mica powder. After sintering and carbonization, glucose is decomposed by heat to form a dense carbon layer. As an activator, potassium hydroxide can form pores on the surface of the dense carbon layer, thereby achieving the synthesis of a porous carbon layer on the surface of mica powder, resulting in a porous carbon layer coated with mica powder.
[0024] Furthermore, during the A2 reaction process described above, the porous carbon layer coating mica powder surface contains a large number of porous structures, which have high adsorption performance, allowing borosilicate glass powder to be adsorbed into the pores on the surface of the porous carbon layer coating mica powder, thus obtaining modified mica powder.
[0025] Furthermore, in the A3 reaction process described above, polyvinyl alcohol and chitosan are used as aerogel matrix, and modified mica powder and aluminum hypophosphite are added to the aerogel matrix to achieve the embedding of modified mica powder and aluminum hypophosphite into the aerogel matrix, thereby obtaining flame-retardant mica powder.
[0026] Further, in step A1, the mass ratio of mica powder, glucose, potassium hydroxide and deionized water is (2-2.5):(1-1.2):(1.2-1.5):(50-60).
[0027] Further, in step A2, the mass ratio of borosilicate glass powder, ethanol and porous carbon-coated mica powder is (0.8-1):(80-100):(2.5-3).
[0028] Further, in step A3, the mass ratio of chitosan, polyvinyl alcohol, aqueous acetic acid solution, glutaraldehyde, modified mica powder and aluminum hypophosphite is (3.8-4):(3.8-4):(90-100):(0.1-0.2):(2-2.3):(1.5-1.7).
[0029] The present invention has the following beneficial effects:
[0030] (1) In the technical solution of the present invention, a porous carbon layer is synthesized on the surface of mica powder to obtain a porous carbon layer coating mica powder. The mica powder with a layered structure can form a dense barrier in the fire-resistant mica filling layer, improve the heat insulation and oxygen isolation effect, delay the thermal damage of the inner rubber insulation, and improve the fire resistance of the cable. Moreover, the synthesized porous carbon skeleton forms a continuous carbon layer in the fire-resistant mica filling layer, further blocking heat transfer and improving the fire resistance of the cable.
[0031] (2) In the technical solution of the present invention, borosilicate glass powder is adsorbed into the pores of the mica powder surface coated by the porous carbon layer. During the high-temperature combustion process of the cable, the temperature is above 800°C, which causes the borosilicate glass powder to soften and melt, forming a fluid molten glass phase. The molten glass phase spreads on the surface of the mica sheet through the porous carbon interconnection channel, bonding the mica sheet to each other, and constructing a continuous and dense inorganic ceramic barrier layer in the inner layer of the cable. Its molten glass phase acts as a bonding phase, bonding the mica sheet into a dense barrier to prevent the mica powder from loosely stacking the sheet during the high-temperature combustion process. Its gaps are large, and flames and oxygen can easily penetrate, significantly enhancing the fire resistance of the cable and delaying the thermal damage of the inner rubber insulation layer.
[0032] (3) In the technical solution of the present invention, modified mica powder, aluminum hypophosphite, polyvinyl alcohol and chitosan are mixed and reacted to realize the embedding of modified mica powder and aluminum hypophosphite into the aerogel matrix. On the one hand, polyvinyl alcohol and chitosan serve as the aerogel skeleton, so that modified mica powder and aluminum hypophosphite are uniformly dispersed in the fire-resistant mica filler, forming a uniformly distributed fire-resistant mica filler layer on the surface of the insulated cable core material, improving the fire resistance of the cable. In addition, during the combustion process, polyvinyl alcohol and chitosan provide carbon source, which can form a dense carbon layer and improve the fire resistance of the cable. On the other hand, during the combustion process, aluminum hypophosphite decomposes to generate non-combustible phosphate solids, further isolating the entry of combustible gases and combustion-supporting gases, thus protecting the cable. In addition, aluminum hypophosphite can also catalyze carbonization, catalyzing polyvinyl alcohol and chitosan to form a dense carbon layer, thereby improving the fire resistance of the cable.
[0033] (4) In the technical solution of the present invention, fire-resistant mica filler, fire-resistant shielding material and fire-resistant flame-retardant sheath material are extruded onto the surface of the insulating cable core material in sequence to form a fireproof cable with a fire-resistant mica filler layer, a fire-resistant shielding layer and a fire-resistant flame-retardant sheath layer on the surface in sequence; the three-layer structure is tightly bonded and has a uniform structure, which reduces interlayer gap defects and effectively prevents flames and heat from penetrating and burning along the interlayer channels;
[0034] Among them, the fire-resistant and flame-retardant sheath layer, as the first fireproof layer, is the outermost layer of the cable. It uses epoxy resin E51 as the matrix and is combined with carbon fiber, zinc phytate and aluminum acetate to form a flame-retardant system. It can catalyze the dehydration and cross-linking of epoxy resin into carbon, which can significantly reduce the release of combustible small molecules. At the same time, the zinc oxide generated by decomposition can capture combustion free radicals, achieving excellent flame-retardant and smoke-suppressing effects, providing the first high-strength fire protection for the inner structure of the cable.
[0035] As the second fireproof layer, the fire-resistant shielding layer ensures the stability of cable power transmission and signal transmission. Zinc borate has the functions of highly efficient smoke suppression, capturing combustion free radicals, and inhibiting interlayer cross-flammation. At the same time, it can buffer the difference in thermal expansion coefficient between the first and third fireproof layers, alleviate interlayer thermal stress under high temperature and cold-heat alternating conditions, and avoid interface delamination and cracking defects in the multi-layer covering structure.
[0036] As a third fireproof layer, the fire-resistant mica filling layer can block heat transfer, making it difficult for flames and oxygen to penetrate, delaying the thermal damage of the inner rubber insulation layer, and significantly enhancing the fire resistance of the cable. Detailed Implementation
[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0038] The raw materials used in the embodiments of this invention are shown below, and all reagents used are analytical grade.
[0039] The rubber insulation material is made of EPDM rubber, stearic acid, dicumyl peroxide crosslinking agent, antioxidant 1010, and aluminum hydroxide in a mass ratio of 10:0.2:0.25:0.1:2.
[0040] The ethylene-vinyl acetate copolymer, product number P815473, contains 12% vinyl acetate and has a melt index of 8 g / 10 min (190℃ / 2.16 kg); the polyethylene wax, product number P903665, has a Mn of 2000-3000; the polyvinyl alcohol, product number 767382, has a Mw of 9000-10000; the chitosan, product number C660110, has a degree of deacetylation ≥85% and a MW of 800000; and the epoxy resin, product number E51, has an E871957. All of these were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.
[0041] The mica powder is a layered mica powder with a particle size of 10µm and a sheet thickness of 500nm; the carbon fiber has a length of 2µm and a diameter of 0.2µm.
[0042] Borosilicate glass powder, 13µm, 99% purity, purchased from Suzhou Qiuyi New Materials Co., Ltd.
[0043] The curing agent is ethylenediamine.
[0044] Example 1: A method for preparing a fire-resistant cable with a multi-layer fire-resistant structure, comprising the following steps:
[0045] S1. Five copper wires with a diameter of 2mm are twisted together to form a cable core. Rubber insulation material is then wrapped around the surface of the cable core and cured at 150℃ and 8MPa for 2 hours to obtain an insulated cable core with an insulation layer thickness of 0.5mm.
[0046] S2. Fire-resistant mica filler, fire-resistant shielding material and fire-resistant flame-retardant sheathing material are sequentially extruded onto the surface of the insulated cable core material to form a fire-resistant cable with a fire-resistant mica filler layer, a flame-retardant shielding layer and a fire-resistant flame-retardant sheathing layer on the surface in sequence, which is a fire-resistant cable with a multi-layer fire-resistant structure.
[0047] Extrusion is carried out in an extruder. The extrusion temperature for refractory mica filler is 180℃; the extrusion temperature for refractory shielding material is 160℃; and the extrusion temperature for refractory flame-retardant sheath material is 140℃.
[0048] The thickness of the fire-resistant mica filling layer is 1mm; the thickness of the fire-resistant shielding layer is 1mm; and the thickness of the fire-resistant and flame-retardant sheath layer is 3mm.
[0049] The fire-resistant mica filler is composed of ethylene-vinyl acetate copolymer, flame-retardant mica powder, dicumyl peroxide and polyethylene wax in a mass ratio of 10:1.5:0.1:0.05;
[0050] The refractory shielding material is composed of ethylene-vinyl acetate copolymer, conductive carbon black, antioxidant 1010, polyethylene wax, and zinc borate mixed in a mass ratio of 10:3:0.1:0.2:0.5.
[0051] The fire-resistant and flame-retardant sheath material is composed of epoxy resin E51, carbon fiber, ethylenediamine, zinc phytate, and aluminum acetate in a mass ratio of 10:0.5:1.2:1:1.2.
[0052] Flame-retardant mica powder is prepared by the following steps:
[0053] A1. Mica powder was placed in a mixture of glucose, potassium hydroxide, and deionized water. After impregnation, it was removed and dried in an oven at 100°C until the moisture evaporated. Then, it was placed in a tube furnace, nitrogen gas was introduced, and it was carbonized at 700°C for 3 hours. After removal, it was cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C until the moisture evaporated to obtain porous carbon-coated mica powder. The mass ratio of mica powder, glucose, potassium hydroxide, and deionized water was 2:1:1.2:50.
[0054] A2. Borosilicate glass powder and ethanol were mixed evenly, and porous carbon-coated mica powder was added. The mixture was stirred and adsorbed at -0.05 MPa for 30 min. After filtration, the mixture was washed three times with deionized water and dried in an oven at 100℃ until the ethanol evaporated to obtain modified mica powder. The mass ratio of borosilicate glass powder, ethanol and porous carbon-coated mica powder was 0.8:80:2.5.
[0055] A3. Chitosan and polyvinyl alcohol were dissolved in a 3% (w / w) aqueous acetic acid solution. The solution was stirred at 95°C and 200 rpm until completely dissolved. After cooling to room temperature, glutaraldehyde, modified mica powder, and aluminum hypophosphite were added. The solution was stirred at 1000 rpm for 5 min and then placed in a freeze dryer. The solution was freeze-dried at -20°C for 24 h to obtain an aerogel, i.e., flame-retardant mica powder. The mass ratio of chitosan, polyvinyl alcohol, aqueous acetic acid solution, glutaraldehyde, modified mica powder, and aluminum hypophosphite was 3.8:3.8:90:0.1:2:1.5.
[0056] Example 2: A method for preparing a fire-resistant cable with a multi-layer fire-resistant structure, comprising the following steps:
[0057] S1. Twist eight copper wires with a diameter of 2.5mm together to form a cable core. Cover the surface of the cable core with rubber insulation material and cure at 170℃ and 9MPa for 3 hours to obtain an insulated cable core with an insulation layer thickness of 0.8mm.
[0058] S2. Fire-resistant mica filler, fire-resistant shielding material and fire-resistant flame-retardant sheathing material are sequentially extruded onto the surface of the insulated cable core material to form a fire-resistant cable with a fire-resistant mica filler layer, a flame-retardant shielding layer and a fire-resistant flame-retardant sheathing layer on the surface in sequence, which is a fire-resistant cable with a multi-layer fire-resistant structure.
[0059] The extrusion process is carried out in an extruder. The extrusion temperature for refractory mica filler is 190℃; the extrusion temperature for refractory shielding material is 170℃; and the extrusion temperature for refractory flame-retardant sheath material is 150℃.
[0060] The thickness of the fire-resistant mica filling layer is 1.5 mm; the thickness of the fire-resistant shielding layer is 1.5 mm; and the thickness of the fire-resistant and flame-retardant sheath layer is 3.5 mm.
[0061] The fire-resistant mica filler is composed of ethylene-vinyl acetate copolymer, flame-retardant mica powder, dicumyl peroxide and polyethylene wax in a mass ratio of 10:1.8:0.15:0.06;
[0062] The refractory shielding material is composed of ethylene-vinyl acetate copolymer, conductive carbon black, antioxidant 1010, polyethylene wax, and zinc borate mixed in a mass ratio of 10:4:0.15:0.3:0.8.
[0063] The fire-resistant and flame-retardant sheath material is composed of epoxy resin E51, carbon fiber, ethylenediamine, zinc phytate, and aluminum acetate in a mass ratio of 10:0.6:1.3:1.3:1.4.
[0064] Flame-retardant mica powder is prepared by the following steps:
[0065] A1. Mica powder was placed in a mixture of glucose, potassium hydroxide, and deionized water. After impregnation, it was removed and dried in an oven at 100°C until the moisture evaporated. Then, it was placed in a tube furnace, nitrogen gas was introduced, and it was carbonized at 750°C for 3.5 hours. After removal, it was cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C until the moisture evaporated to obtain porous carbon-coated mica powder. The mass ratio of mica powder, glucose, potassium hydroxide, and deionized water was 2.3:1.1:1.3:55.
[0066] A2. Borosilicate glass powder and ethanol were mixed evenly, and porous carbon-coated mica powder was added. The mixture was stirred and adsorbed at -0.03 MPa for 35 min. After filtration, the mixture was washed three times with deionized water and dried in an oven at 100℃ until the ethanol evaporated to obtain modified mica powder. The mass ratio of borosilicate glass powder, ethanol and porous carbon-coated mica powder was 0.9:90:2.8.
[0067] A3. Chitosan and polyvinyl alcohol were dissolved in a 3% (w / w) aqueous acetic acid solution. The solution was stirred at 98℃ and 210 r / min until completely dissolved. After cooling to room temperature, glutaraldehyde, modified mica powder, and aluminum hypophosphite were added. The solution was stirred at 1300 r / min for 8 min and then placed in a freeze dryer. The solution was freeze-dried at -20℃ for 24 h to obtain an aerogel, i.e., flame-retardant mica powder. The mass ratio of chitosan, polyvinyl alcohol, aqueous acetic acid solution, glutaraldehyde, modified mica powder, and aluminum hypophosphite was 3.9:3.9:95:0.15:2.2:1.6.
[0068] Example 3: A method for preparing a fire-resistant cable with a multi-layer fire-resistant structure, comprising the following steps:
[0069] S1. Twist 10 copper wires with a diameter of 3mm together to form a cable core material, cover the surface of the cable core material with rubber insulation material, and cure at 190℃ and 10MPa for 4 hours to obtain an insulated cable core material with an insulation layer thickness of 1mm.
[0070] S2. Fire-resistant mica filler, fire-resistant shielding material and fire-resistant flame-retardant sheathing material are sequentially extruded onto the surface of the insulated cable core material to form a fire-resistant cable with a fire-resistant mica filler layer, a flame-retardant shielding layer and a fire-resistant flame-retardant sheathing layer on the surface in sequence, which is a fire-resistant cable with a multi-layer fire-resistant structure.
[0071] Extrusion is carried out in an extruder. The extrusion temperature for refractory mica filler is 200℃; the extrusion temperature for refractory shielding material is 180℃; and the extrusion temperature for refractory flame-retardant sheath material is 160℃.
[0072] The thickness of the fire-resistant mica filling layer is 2mm; the thickness of the fire-resistant shielding layer is 2mm; and the thickness of the fire-resistant and flame-retardant sheath layer is 4mm.
[0073] The fire-resistant mica filler is composed of ethylene-vinyl acetate copolymer, flame-retardant mica powder, dicumyl peroxide and polyethylene wax in a mass ratio of 10:2:0.2:0.07;
[0074] The refractory shielding material is composed of ethylene-vinyl acetate copolymer, conductive carbon black, antioxidant 1010, polyethylene wax, and zinc borate mixed in a mass ratio of 10:5:0.2:0.4:1.
[0075] The fire-resistant and flame-retardant sheath material is composed of epoxy resin E51, carbon fiber, ethylenediamine, zinc phytate, and aluminum acetate in a mass ratio of 10:0.7:1.5:1.5:1.6.
[0076] Flame-retardant mica powder is prepared by the following steps:
[0077] A1. Mica powder was placed in a mixture of glucose, potassium hydroxide, and deionized water. After impregnation, it was removed and dried in an oven at 100°C until the moisture evaporated. Then, it was placed in a tube furnace, nitrogen gas was introduced, and it was carbonized at 800°C for 4 hours. After removal, it was cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C until the moisture evaporated to obtain porous carbon-coated mica powder. The mass ratio of mica powder, glucose, potassium hydroxide, and deionized water was 2.5:1.2:1.5:60.
[0078] A2. Borosilicate glass powder and ethanol were mixed evenly, and porous carbon-coated mica powder was added. The mixture was stirred and adsorbed at -0.02 MPa for 40 min. After filtration, the mixture was washed three times with deionized water and dried in an oven at 100℃ until the ethanol evaporated to obtain modified mica powder. The mass ratio of borosilicate glass powder, ethanol and porous carbon-coated mica powder was 1:100:3.
[0079] A3. Chitosan and polyvinyl alcohol were dissolved in a 3% (w / w) aqueous acetic acid solution. The solution was stirred at 100℃ and 220 r / min until completely dissolved. After cooling to room temperature, glutaraldehyde, modified mica powder, and aluminum hypophosphite were added. The mixture was stirred at 1500 r / min for 5-10 min and then placed in a freeze dryer. The mixture was freeze-dried at -20℃ for 24 h to obtain an aerogel, i.e., flame-retardant mica powder. The mass ratio of chitosan, polyvinyl alcohol, aqueous acetic acid solution, glutaraldehyde, modified mica powder, and aluminum hypophosphite was 4:4:100:0.2:2.3:1.7.
[0080] Comparative Example 1
[0081] The only difference between this comparative example and Example 3 is the preparation of the flame-retardant mica powder, as detailed below:
[0082] Flame-retardant mica powder is prepared by the following steps:
[0083] A1. Borosilicate glass powder and ethanol were mixed evenly, mica powder was added, and the mixture was stirred and adsorbed at -0.02 MPa for 40 min. After filtration, the mixture was washed three times with deionized water and dried in an oven at 100℃ until the ethanol evaporated to obtain modified mica powder. The mass ratio of borosilicate glass powder, ethanol and mica powder was 1:100:3.
[0084] A2. Chitosan and polyvinyl alcohol were dissolved in a 3% (w / w) aqueous acetic acid solution. The solution was stirred at 100℃ and 220 r / min until completely dissolved. After cooling to room temperature, glutaraldehyde, modified mica powder, and aluminum hypophosphite were added. The mixture was stirred at 1500 r / min for 5-10 min and then placed in a freeze dryer. The mixture was freeze-dried at -20℃ for 24 h to obtain an aerogel, i.e., flame-retardant mica powder. The mass ratio of chitosan, polyvinyl alcohol, aqueous acetic acid solution, glutaraldehyde, modified mica powder, and aluminum hypophosphite was 4:4:100:0.2:2.3:1.7.
[0085] Comparative Example 2
[0086] The only difference between this comparative example and Example 3 is the preparation of the flame-retardant mica powder, as detailed below:
[0087] Flame-retardant mica powder is prepared by the following steps:
[0088] A1. Mica powder was placed in a mixture of glucose, potassium hydroxide, and deionized water. After impregnation, it was removed and dried in an oven at 100°C until the moisture evaporated. Then, it was placed in a tube furnace, nitrogen gas was introduced, and it was carbonized at 800°C for 4 hours. After removal, it was cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C until the moisture evaporated to obtain porous carbon-coated mica powder. The mass ratio of mica powder, glucose, potassium hydroxide, and deionized water was 2.5:1.2:1.5:60.
[0089] A2. Chitosan and polyvinyl alcohol were dissolved in a 3% (w / w) aqueous acetic acid solution. The solution was stirred at 100℃ and 220 r / min until completely dissolved. After cooling to room temperature, glutaraldehyde, porous carbon-coated mica powder, and aluminum hypophosphite were added. The mixture was stirred at 1500 r / min for 5-10 min and then placed in a freeze dryer. The mixture was freeze-dried at -20℃ for 24 h to obtain an aerogel, i.e., flame-retardant mica powder. The mass ratio of chitosan, polyvinyl alcohol, aqueous acetic acid solution, glutaraldehyde, porous carbon-coated mica powder, and aluminum hypophosphite was 4:4:100:0.2:2.3:1.7.
[0090] Comparative Example 3
[0091] The only difference between this comparative example and Example 3 is the preparation of the flame-retardant mica powder, as detailed below:
[0092] Flame-retardant mica powder is prepared by the following steps:
[0093] A1. Mica powder was placed in a mixture of glucose, potassium hydroxide, and deionized water. After impregnation, it was removed and dried in an oven at 100°C until the moisture evaporated. Then, it was placed in a tube furnace, nitrogen gas was introduced, and it was carbonized at 800°C for 4 hours. After removal, it was cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C until the moisture evaporated to obtain porous carbon-coated mica powder. The mass ratio of mica powder, glucose, potassium hydroxide, and deionized water was 2.5:1.2:1.5:60.
[0094] A2. Borosilicate glass powder and ethanol were mixed evenly, and porous carbon-coated mica powder was added. The mixture was stirred and adsorbed at -0.02 MPa for 40 min. After filtration, the mixture was washed three times with deionized water and dried in an oven at 100℃ until the ethanol evaporated to obtain modified mica powder. The mass ratio of borosilicate glass powder, ethanol and porous carbon-coated mica powder was 1:100:3.
[0095] A3. Chitosan and polyvinyl alcohol were dissolved in a 3% (w / w) aqueous acetic acid solution. The solution was stirred at 100℃ and 220r / min until completely dissolved. After cooling to room temperature, glutaraldehyde and modified mica powder were added. The mixture was stirred at 1500r / min for 5-10 min and then placed in a freeze dryer. The mixture was freeze-dried at -20℃ for 24 h to obtain an aerogel, i.e., flame-retardant mica powder. The mass ratio of chitosan, polyvinyl alcohol, aqueous acetic acid solution, glutaraldehyde, and modified mica powder was 4:4:100:0.2:4.
[0096] Comparative Example 4
[0097] The only difference between this comparative example and Example 3 is the preparation of the flame-retardant mica powder, as detailed below:
[0098] Flame-retardant mica powder is prepared by the following steps:
[0099] A1. Mica powder was placed in a mixture of glucose, potassium hydroxide, and deionized water. After impregnation, it was removed and dried in an oven at 100°C until the moisture evaporated. Then, it was placed in a tube furnace, nitrogen gas was introduced, and it was carbonized at 800°C for 4 hours. After removal, it was cooled to room temperature, washed three times with deionized water, and dried in an oven at 100°C until the moisture evaporated to obtain porous carbon-coated mica powder. The mass ratio of mica powder, glucose, potassium hydroxide, and deionized water was 2.5:1.2:1.5:60.
[0100] A2. Borosilicate glass powder and ethanol were mixed evenly, and porous carbon-coated mica powder was added. The mixture was stirred and adsorbed at -0.02 MPa for 40 min. After filtration, the mixture was washed three times with deionized water and dried in an oven at 100℃ until the ethanol evaporated to obtain modified mica powder. The mass ratio of borosilicate glass powder, ethanol and porous carbon-coated mica powder was 1:100:3.
[0101] A3. Polyvinyl alcohol was dissolved in a 3% (w / w) aqueous acetic acid solution and stirred at 100℃ and 220 r / min until completely dissolved. After cooling to room temperature, glutaraldehyde, modified mica powder, and aluminum hypophosphite were added. After stirring at 1500 r / min for 5-10 min, the mixture was placed in a freeze dryer and freeze-dried at -20℃ for 24 h to obtain an aerogel, i.e., flame-retardant mica powder. The mass ratio of polyvinyl alcohol, aqueous acetic acid solution, glutaraldehyde, modified mica powder, and aluminum hypophosphite was 8:100:0.2:2.3:1.7.
[0102] Comparative Example 5
[0103] The only difference between this comparative example and Example 3 is the preparation of the fire-resistant cable with a multi-layer fire-resistant structure, as detailed below:
[0104] A method for preparing a fire-resistant cable with a multi-layer fire-resistant structure includes the following steps:
[0105] S1. Twist 10 copper wires with a diameter of 3mm together to form a cable core material, cover the surface of the cable core material with rubber insulation material, and cure at 190℃ and 10MPa for 4 hours to obtain an insulated cable core material with an insulation layer thickness of 1mm.
[0106] S2. Fire-resistant mica filler and fire-resistant shielding material are extruded onto the surface of the insulated cable core material in sequence to form a fire-resistant cable with a fire-resistant mica filler layer and a flame-retardant shielding layer on the surface in sequence, which is a fire-resistant cable with a multi-layer fire-resistant structure.
[0107] Extrusion is carried out in an extruder. The extrusion temperature for refractory mica filler is 200℃; the extrusion temperature for refractory shielding material is 180℃; and the extrusion temperature for refractory flame-retardant sheath material is 160℃.
[0108] The thickness of the fire-resistant mica filling layer is 2mm; the thickness of the fire-resistant shielding layer is 2mm.
[0109] The fire-resistant mica filler is composed of ethylene-vinyl acetate copolymer, flame-retardant mica powder, dicumyl peroxide and polyethylene wax in a mass ratio of 10:2:0.2:0.07;
[0110] The refractory shielding material is composed of ethylene-vinyl acetate copolymer, conductive carbon black, antioxidant 1010, polyethylene wax, and zinc borate in a mass ratio of 10:5:0.2:0.4:1.
[0111] Comparative Example 6
[0112] The only difference between this comparative example and Example 3 is the preparation of the fire-resistant cable with a multi-layer fire-resistant structure, as detailed below:
[0113] A method for preparing a fire-resistant cable with a multi-layer fire-resistant structure includes the following steps:
[0114] S1. Twist 10 copper wires with a diameter of 3mm together to form a cable core material, cover the surface of the cable core material with rubber insulation material, and cure at 190℃ and 10MPa for 4 hours to obtain an insulated cable core material with an insulation layer thickness of 1mm.
[0115] S2. Fire-resistant mica filler and fire-resistant flame-retardant sheath material are extruded onto the surface of the insulated cable core material in sequence to form a fire-resistant cable with a fire-resistant mica filler layer and a fire-resistant flame-retardant sheath layer on the surface in sequence, which is a fire-resistant cable with a multi-layer fire-resistant structure.
[0116] Extrusion is carried out in an extruder. The extrusion temperature for refractory mica filler is 200℃; the extrusion temperature for refractory shielding material is 180℃; and the extrusion temperature for refractory flame-retardant sheath material is 160℃.
[0117] The thickness of the fire-resistant mica filling layer is 2mm; the thickness of the fire-resistant and flame-retardant sheath layer is 4mm.
[0118] The fire-resistant mica filler is composed of ethylene-vinyl acetate copolymer, flame-retardant mica powder, dicumyl peroxide and polyethylene wax in a mass ratio of 10:2:0.2:0.07;
[0119] The fire-resistant and flame-retardant sheath material is made by mixing epoxy resin E51, carbon fiber, ethylenediamine, zinc phytate and aluminum acetate in a mass ratio of 10:0.7:1.5:1.5:1.6.
[0120] The performance of the fire-resistant cables prepared in Examples 1-3 and Comparative Examples 1-6 was then tested.
[0121] The limiting oxygen index of the fire-resistant cable prepared above was determined according to GB / T2406.1-2008 standard.
[0122] The fire-resistant cable prepared above was cut into 15cm lengths and placed vertically. It was then burned with a 1000W flame torch for 10 seconds. After that, the burning was stopped and the duration of the flame was recorded. The burn rate was calculated based on the state of the cable before and after burning, and the loss state of the insulation layer after burning was observed.
[0123] As shown in Table 1 below.
[0124] Table 1. Performance testing of fire-resistant cables prepared in Examples 1-3 and Comparative Examples 1-6
[0125]
[0126] As can be seen from the data in Table 1, the fire-resistant cables prepared in Examples 1-3 have high fire resistance and can effectively prevent flames and heat from penetrating and burning along the interlayer channels.
[0127] Comparative Example 1 replaced the porous carbon-coated mica powder with flame-retardant mica powder prepared from mica powder and added it to the fire-resistant and flame-retardant sheath material to prepare a fire-resistant cable with a multi-layer fire-resistant structure. Its performance decreased, which proved that the synthesis of a porous carbon layer on the surface of mica powder and the formation of a continuous carbon layer in the fire-resistant mica filling layer can block heat transfer, inhibit the thermal decomposition of the fire-resistant mica filling layer, and improve the fire resistance of the cable. Moreover, the molten glass phase spreads on the surface of the mica sheet through the porous carbon interconnecting channels, bonding the sheet mica to each other and constructing a continuous and dense inorganic ceramic barrier layer in the inner layer of the cable. Its molten glass phase acts as a binder phase, bonding the mica sheets into a dense barrier to prevent the mica powder from loosely stacking the sheet during high-temperature combustion. Its large gaps allow flames and oxygen to easily penetrate, significantly enhancing the fire resistance of the cable and delaying the thermal damage of the inner rubber insulation layer.
[0128] Comparative Example 2 showed that flame-retardant mica powder prepared by replacing modified mica powder with porous carbon-coated mica powder was added to the fire-resistant and flame-retardant sheath material to prepare a fire-resistant cable with a multi-layer fire-resistant structure. The cable's performance decreased, demonstrating that borosilicate glass powder adsorbs into the pores on the surface of the porous carbon-coated mica powder. During high-temperature combustion, the borosilicate glass powder slowly releases boron-oxygen free radicals, capturing combustion free radicals and terminating the free radical oxidation reaction, achieving a good flame-retardant effect. Furthermore, during high-temperature combustion, the temperature... At temperatures above 800℃, the borosilicate glass powder softens and melts, forming a fluid molten glass phase. This molten glass phase spreads on the surface of the mica sheets through porous carbon interconnected channels, bonding the mica sheets together to form a continuous and dense inorganic ceramic barrier layer in the inner layer of the cable. The molten glass phase acts as a binder, binding the mica sheets into a dense barrier to prevent the mica powder from loosely stacking during high-temperature combustion. Its large gaps allow flames and oxygen to easily penetrate, significantly enhancing the fire resistance of the cable and delaying the thermal damage to the inner rubber insulation layer.
[0129] Comparative Example 3, in which aluminum hypophosphite was replaced by modified mica powder at a certain mass, and Comparative Example 4, in which chitosan was replaced by polyvinyl alcohol at a certain mass, were added to fire-resistant and flame-retardant sheathing materials to prepare fire-resistant cables with multi-layer fire-resistant structures. The performance of these cables decreased, demonstrating that mixing modified mica powder, aluminum hypophosphite, polyvinyl alcohol, and chitosan allows for the embedding of modified mica powder and aluminum hypophosphite into the aerogel matrix. Polyvinyl alcohol and chitosan act as the aerogel skeleton, ensuring that the modified mica powder and aluminum hypophosphite are uniformly dispersed in the fire-resistant mica filler, forming a uniformly distributed fire-resistant structure on the surface of the insulated cable core. The pyrophosphorus filling layer improves the fire resistance of the cable. During combustion, polyvinyl alcohol and chitosan provide carbon sources, forming a dense carbon layer that enhances the cable's fire resistance. During combustion, aluminum hypophosphite decomposes to generate free radicals. Combustion of these free radicals terminates the free radical reaction, achieving a good fire-retardant effect. Furthermore, the decomposition of aluminum hypophosphite generates non-combustible phosphate solids, further isolating the cable from flammable and combustion-supporting gases. In addition, aluminum hypophosphite also catalyzes char formation, catalyzing the formation of a dense carbon layer from polyvinyl alcohol and chitosan, thus improving the cable's fire resistance.
[0130] Comparative Example 5 (without fire-resistant and flame-retardant sheath) and Comparative Example 6 (without fire-resistant shielding layer) were used to prepare fire-resistant cables with multi-layer fire-resistant structures. Their performance declined, demonstrating that the fire-resistant and flame-retardant sheath, as the first fireproof layer and the outermost layer of the cable, uses epoxy resin E51 as the matrix and is combined with a flame-retardant system of carbon fiber, zinc phytate, and aluminum acetate. This system can catalyze the dehydration and cross-linking of epoxy resin into carbon, significantly reducing the release of combustible small molecules. At the same time, the zinc oxide generated by decomposition can capture combustion free radicals, achieving excellent flame-retardant and smoke-suppressing effects, providing the first high-strength fire protection for the inner structure of the cable. The fire-resistant shielding layer, as the second fireproof layer, ensures the stability of cable power transmission and signal transmission. Zinc borate has efficient smoke suppression, captures combustion free radicals, and inhibits interlayer cross-flame propagation. It can also buffer the difference in thermal expansion coefficients between the first and third fireproof layers, alleviate interlayer thermal stress under high-temperature and alternating hot and cold conditions, and avoid interface delamination and cracking defects in the multi-layer sheath structure.
[0131] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0132] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A method for preparing a fire-resistant cable with a multi-layer fire-resistant structure, characterized in that, Includes the following steps: S1. Copper wire is stranded to obtain cable core material. Rubber insulation material is coated on the surface of the cable core material and cured to obtain insulated cable core material. S2. Fire-resistant mica filler, fire-resistant shielding material and fire-resistant flame-retardant sheathing material are sequentially extruded onto the surface of the insulated cable core material to form a fire-resistant cable with a fire-resistant mica filler layer, a flame-retardant shielding layer and a fire-resistant flame-retardant sheathing layer on the surface in sequence, which is a fire-resistant cable with a multi-layer fire-resistant structure. The fire-resistant mica filler is composed of ethylene-vinyl acetate copolymer, flame-retardant mica powder, dicumyl peroxide and polyethylene wax in a mass ratio of 10:(1.5-2):(0.1-0.2):(0.05-0.07). The flame-retardant mica powder is obtained by synthesizing a porous carbon layer on the surface of mica powder, and then loading borosilicate glass powder to obtain modified mica powder; it is also obtained by mixing and reacting modified mica powder, aluminum hypophosphite, polyvinyl alcohol and chitosan. The refractory shielding material is composed of ethylene-vinyl acetate copolymer, conductive carbon black, antioxidant 1010, polyethylene wax, and zinc borate in a mass ratio of 10:(3-5):(0.1-0.2):(0.2-0.4):(0.5-1). The fire-resistant and flame-retardant sheath material is composed of epoxy resin E51, carbon fiber, curing agent, zinc phytate and aluminum acetate in a mass ratio of 10:(0.5-0.7):(1.2-1.5):(1-1.5):(1.2-1.6).
2. The method for preparing a fire-resistant cable with a multi-layer fire-resistant structure according to claim 1, characterized in that, The flame-retardant mica powder is prepared by the following steps: A1. Place mica powder in a mixture of glucose, potassium hydroxide and deionized water. After impregnation, remove it and dry it until the water evaporates. Place it in a tube furnace, introduce nitrogen gas, and carbonize it at 700-800℃ for 3-4 hours. Remove it, cool it to room temperature, wash it, and dry it until the water evaporates to obtain porous carbon-coated mica powder. A2. Mix borosilicate glass powder and ethanol evenly, add porous carbon layer to coat mica powder, stir and adsorb at -0.05~-0.02MPa for 30-40min, filter, wash, and dry until ethanol evaporates to obtain modified mica powder. A3. Dissolve chitosan and polyvinyl alcohol in an aqueous acetic acid solution, stir at 95-100℃ and 200-220r / min until completely dissolved, cool to room temperature, add glutaraldehyde, modified mica powder, and aluminum hypophosphite, stir at 1000-1500r / min for 5-10 min, and freeze-dry to obtain aerogel, i.e. flame-retardant mica powder.
3. The method for preparing a fire-resistant cable with a multi-layer fire-resistant structure according to claim 2, characterized in that, In step A1, the mass ratio of mica powder, glucose, potassium hydroxide and deionized water is (2-2.5):(1-1.2):(1.2-1.5):(50-60).
4. The method for preparing a fire-resistant cable with a multi-layer fire-resistant structure according to claim 2, characterized in that, In step A2, the mass ratio of borosilicate glass powder, ethanol and porous carbon-coated mica powder is (0.8-1):(80-100):(2.5-3).
5. The method for preparing a fire-resistant cable with a multi-layer fire-resistant structure according to claim 2, characterized in that, In step A3, the mass ratio of chitosan, polyvinyl alcohol, aqueous acetic acid solution, glutaraldehyde, modified mica powder and aluminum hypophosphite is (3.8-4):(3.8-4):(90-100):(0.1-0.2):(2-2.3):(1.5-1.7).
6. The method for preparing a fire-resistant cable with a multi-layer fire-resistant structure according to claim 1, characterized in that, In step S1, the stranding process specifically involves stranding 5-10 copper wires with a diameter of 2-3 mm together to form a cable core.
7. The method for preparing a fire-resistant cable with a multi-layer fire-resistant structure according to claim 1, characterized in that, In step S1, the thickness of the rubber insulation layer is 0.5-1mm; In step S1, the curing process specifically involves curing at 150-190℃ and 8-10MPa for 2-4 hours.
8. A method for preparing a fire-resistant cable with a multi-layer fire-resistant structure according to claim 1, characterized in that, In step S2, the extrusion is carried out in an extruder, and the extrusion temperature of the refractory mica filler is 180-200℃; the extrusion temperature of the refractory shielding material is 160-180℃; and the extrusion temperature of the refractory flame-retardant sheath material is 140-160℃.
9. A method for preparing a fire-resistant cable with a multi-layer fire-resistant structure according to claim 1, characterized in that, In step S2, the thickness of the fire-resistant mica filling layer is 1-2 mm; the thickness of the fire-resistant shielding layer is 1-2 mm; and the thickness of the fire-resistant and flame-retardant sheath layer is 3-4 mm.
10. A fire-resistant cable with a multi-layer fire-resistant structure prepared by the method of preparing a fire-resistant cable with a multi-layer fire-resistant structure as described in any one of claims 1-9.
